2018
DOI: 10.15356/2076-6734-2018-4-462-472
|View full text |Cite
|
Sign up to set email alerts
|

Contemporary changes in the area of glaciers in the western part of the Nordenskjold Land (Svalbard)

Abstract: Climate warming in Svalbard, starting in the 1920s, caused a signifcant reduction in the mountain glaciation of the Nordenskjold Land. Te most extensive changes took place in the Western part of this territory due to the influence of the warm Spitsbergen current creating here the high temperature background. In addition, due to elevation of the level of the climatic snow line, many glaciers have actually lost the area of accumulation. From 1936 to 2017, the area of glaciers in the Western part of this region de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(5 citation statements)
references
References 7 publications
0
5
0
Order By: Relevance
“…This is because glacier size decrease and surface 30 lowering induce shrinking accumulation area and further decreasing warm-based area terminating the recharge of springs. In this context, in the study of Chernov and Muraviev (2018) it was shown that the loss in glacier area in Nordenskiöld Land (West Spitsbergen) between 1936 and 2017 reached 49.5 %. Water discharge by the spring in Grøndalen does not necessarily means that surrounding glaciers are warm-based at current time.…”
Section: Some Aspects Of Pingo Formation In the Context Of Grøndalen mentioning
confidence: 99%
“…This is because glacier size decrease and surface 30 lowering induce shrinking accumulation area and further decreasing warm-based area terminating the recharge of springs. In this context, in the study of Chernov and Muraviev (2018) it was shown that the loss in glacier area in Nordenskiöld Land (West Spitsbergen) between 1936 and 2017 reached 49.5 %. Water discharge by the spring in Grøndalen does not necessarily means that surrounding glaciers are warm-based at current time.…”
Section: Some Aspects Of Pingo Formation In the Context Of Grøndalen mentioning
confidence: 99%
“…The glacier is formed by two tributaries merging in the middle part at the level of 300-360 m a.s.l. Chernov et al [22] reported that from 1936 to 2017, the glacier lost 44% of its area, from 2003 to 2017 it lost 23%, and 27% was lost from 1990 to 2017. The glacier retreated by 3 km from 1936 to 2017 ( Figure 1).…”
Section: Field Measurements and Datamentioning
confidence: 99%
“…According to multi-temporal digital inventory of Svalbard glaciers by Nuth [6] and the original glacier inventory of Svalbard by Hagen [43], which followed the identification and parameter definitions outlined in the World Glacier Inventory [44], the largest relative area changes between the periods of these two inventories occurred in Nordenskiöld Land area. The results from [22] showed that the reduction of valley glaciers of Nordenskiöld Land is inversely proportional to their size. The elevation range is an important factor since it is directly related to the ablation.…”
Section: Comparison With the Other Olaciers Of The Archipelagomentioning
confidence: 99%
“…The degradation of glaciers is widespread in the west of the Nordenskiold Land during the current 100-year period as a result of climate warming (Mavlyudov et al, 2012). From 1936 to 2017, the area of glaciers decreased on average by 49.5%, and their outer edge retreated by several kilometers (Chernov and Murav'ev, 2018). Intraglacial channels are described in a number of glaciers: water through them is drained to bed rocks (Mavlyudov, 2007).…”
Section: Study Areamentioning
confidence: 99%